Point defect properties in high entropy MAX phases from first-principles calculations. (15th April 2023) - Xiao, Hao; Zhao, Shuang; Liu, Qingyuan; Li, Yuxin; Zhao, Shijun; Luo, Fengping; Wang, Yugang; Huang, Qing; Wang, Chenxu
Abstract: MAX phase materials exhibit both metal and ceramic properties due to their unique laminated atomic structures, making them promising candidates in advanced nuclear energy systems. Recently, high entropy MAX (HE-MAX) phases have been developed and attracted much attention due to their unique properties. However, the role of chemical disorder in HE-MAX phases in their point defects properties is still not clear. In this work, we investigated the point defect properties in (TiVNb)2 SnC, (TiZrHf)2 SnC, (TiVNbZrHf)2 SnC, and five corresponding single-component M2 SnC phases (M=Ti, V, Nb, Zr, Hf) using first-principles calculations. The average vacancy (VM, VSn, VC ) formation energies in the HE-MAX phases are (TiZrHf)2 SnC > (TiVNbZrHf)2 SnC > (TiVNb)2 SnC. With the addition of Zr and Hf atoms, the charge transfer between atoms in the HE-MAX phase increases, hindering the formation of these vacancies. Meanwhile, the obtained migration energies show that the migration barrier of VM through Ti is lower than that of V, Nb, Zr, or Hf, while Zr and Hf atoms increase the VC migration barrier due to their large atomic sizes. Additionally, the formation energies of antisite defects in all three HE-MAX phases are lower than the single-component M2 SnC phases, indicating that the HE-MAX phases are more resistant to radiation-induced amorphization. This work provides a fundamental understanding of the effect of chemical disorder on point defect properties in MAX phases and proposes a new strategy for designing novel HE-MAX phases with better performance in nuclear applications. Graphical abstract: Image, graphical abstract